Body proportions according to stature groups in elite athletes - Saco-Ledo, G.; Porta, J.; Monson, T. A.; Brasil, M. F.; Duyar, I. (Research in Sports Medicine, 2022)
The aim of this study was to investigate whether body proportions change as stature increases in elite Spanish athletes. The sample includes a total of 2,030 participants, comprised of 1,357 adult males, and 673 adult females. The male athletes were classified into five groups by stature, and the female athletes were classified separately into four stature groups. Ten anthropometric measurements were collected, and eleven body proportions were calculated. The body proportions with significant differences between stature groups in males were relative arm length (0.53-1.60%), relative forearm length (0.69-2.08%), relative thigh length (1.17-1.56%), relative tibial length (1.37-6.39%), cormic index (-0.94--4.49%), Manouvrier index (1.60-9.60%), and crural index (1.05-4.79%). In females, the body proportions with significant differences were relative forearm length (1.43%), relative thigh length (1.94-3.88%), relative tibial length (2.74-4.56%), cormic index (-0.74--3.72%), and Manouvrier index (1.97-8.71%). The distal parts of the upper and lower limbs increase proportionally as stature increases, whereas relative hand and foot lengths, which are the most distal parts of the extremities, remain constant in elite athletes.